Experiences of Unifesp undergraduates: The evaluation of graduates - Minhoto, Maria Angélica Pedra; Silvestre, Magali Aparecida; Souza, Deise Lopes de; Reis, Regina Célia (Education Policy Analysis Archives, 2022)
This article aims to verify how graduates of different sociodemographic and cultural profiles assess their training experiences at the Universidade Federal de São Paulo (Unifesp) and relate them to their individual growth after the course. Therefore, it investigates the existence of an association between personal characteristics of former students and factors such as development of professional activity in the area of ​​training, ease of getting a job, salary level and continuity of studies. An online questionnaire was applied, with an access link sent by e-mail to graduates undergraduate courses, between the months of April and August 2020. At total of 1,795 responses were obtained. In addition to the questionnaire, the accumulated coefficient of academic performance by each respondent until the end of their course was also used, information taken from the institution's academic record system. In order to verify the effect of passing through Unifesp on different groups of individuals, an indicator was developed to differentiate graduates according to their ethnic-racial belonging and the previous experience of ascending generations in higher education. For data treatment, exploratory factor analysis of the course evaluation questionnaire and Chi-square tests were performed to assess the relationship between qualitative variables. The main results indicate that the experiences at Unifesp were positively evaluated and had an influence on the personal and professional trajectory of the graduates, persisting however inequalities with regard to the ease of employment after the course, the income range and the continuity of studies, depending on ethnic-racial belonging and the previous experience of ascending generations in higher education.